2021
DOI: 10.1371/journal.pone.0260360
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein displays sequence similarities with paramyxovirus surface proteins; a bioinformatics study

Abstract: Recent emergence of SARS-CoV-2 and associated COVID-19 pandemic have posed a great challenge for the scientific community. In this study, we performed bioinformatic analyses on SARS-CoV-2 protein sequences, trying to unravel potential molecular similarities between this newly emerged pathogen with non-coronavirus ssRNA viruses. Comparing the proteins of SARS-CoV-2 with non-coronavirus positive and negative strand ssRNA viruses revealed multiple sequence similarities between SARS-CoV-2 and non-coronaviruses, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Evolutionary conservation of the SARS-CoV-2 spike protein with other single-stranded RNA viruses has also been described, and computational analysis has shown genetic sequence similarities between regions of SARS-CoV-2 and paramyxoviruses including mumps, measles and Nipah viruses 48 . Interestingly, within the spike protein, the region of highest sequence similarity between SARS-CoV-2 and paramyxoviruses corresponds with the SARS-CoV-2 S2 fusion protein domain, which is also highly conserved among HCoVs 48 . The high sequence homology between these viruses and SARS-CoV-2 suggests that viruses other than HCoV may also contribute to SARS-CoV-2 immune cross-reactivity and impact on infection and vaccine outcomes.…”
Section: Sars-cov-2 Sequence Homology With Other Virusesmentioning
confidence: 99%
“…Evolutionary conservation of the SARS-CoV-2 spike protein with other single-stranded RNA viruses has also been described, and computational analysis has shown genetic sequence similarities between regions of SARS-CoV-2 and paramyxoviruses including mumps, measles and Nipah viruses 48 . Interestingly, within the spike protein, the region of highest sequence similarity between SARS-CoV-2 and paramyxoviruses corresponds with the SARS-CoV-2 S2 fusion protein domain, which is also highly conserved among HCoVs 48 . The high sequence homology between these viruses and SARS-CoV-2 suggests that viruses other than HCoV may also contribute to SARS-CoV-2 immune cross-reactivity and impact on infection and vaccine outcomes.…”
Section: Sars-cov-2 Sequence Homology With Other Virusesmentioning
confidence: 99%
“…It is crucial for tracking the transmission dynamics of the SARS-CoV-2 variants between Taiyuan and Wuhan. Our results provide valuable data for researchers and healthcare departments to carefully monitor the evolution of SARS-CoV-2, which can help in controlling the spread of SARS-CoV-2 in particular and other viruses in general [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the mechanism behind such cross-protection revealed that individuals vaccinated with the MMR or tetanus, diphtheria and pertussis (Tdap) vaccine shared TCR clonotypes with individuals who were convalescent or vaccinated against SARS-CoV-2 [ 36 ]. Furthermore, sequence homologies between MMR surface proteins and SARS-CoV-2 spike have been identified that may give rise to cross-reactive T cells [ 136 , 137 ]. This suggests that T cell cross-reactivity between MMR or Tdap and SARS-CoV-2 may result in a cross-protective effect against COVID-19.…”
Section: T Cell Cross-reactivity From the Measles Mumps And Rubella V...mentioning
confidence: 99%